Kebijakan APBN Khalifah Umar bin Khattab - Suleman Jajuli (Institut Agama Islam Sahid Bogor, 2021)
The problem of state finances has always been an actual problem, especially within the scope of Indonesia, starting from the large amount of spending for the needs of state officials, income that is not balanced with expenditures to the problem of unpaid foreign debts. Policies regarding the State Expenditure Revenue Budget became a problem in almost all countries, as did what happened during the Caliphate of Umar bin Khattab in Medina. The many problems of state finances require effective and efficient actions to solve them.Caliph Umar bin Khattab is a state head in Islamic history who has managed to regulate how a country's income can be increased as well as how to regulate state finances so that there is no deficit. Among the policies carried out by Umar bin Khattab are optimizing zakat, kharaj, ushur, jizyah and other state revenues. Meanwhile, from spending, Umar bin Khattab carried out a policy by making expenditures to fulfill the needs of many people, expenditures as a means of retribution for wealth, expenditures that lead to increased effective demands, expenditures related to investment and production and expenditures aimed at reducing the inflation rate by market intervention policy.The essence of Caliph Umar bin Khattab's economic policy was to encourage people to carry out economic activities either individually or in groups without the help of the Baitul Mall. Second, actions or policies to encourage community economic growth with the help of Baitul Mall funds.